The Role of Companies in the Strategic Turn of EU Competition Law - Pastor Merchante, Fernando (Bloomsbury, 2024)
The purpose of this chapter is to reflect upon the role of companies in the transformational change that competition law and policy is currently going through in the European Union (EU). The main causes of the disruption are well known. The EU’s commitment to tackling global warming and climate change, as expressed in the European Green Deal, affects EU competition law and policy. The weight that environmental considerations should have in antitrust and merger control remains controversial, but the movement towards a greener EU competition policy has gained track over the last few years. The objective of transforming the EU economy to make it more sustainable goes hand in hand with the objective of adapting it to the new digital reality. The ramifications of the so-called digital transition are also felt in the area of competition law, if only because of the need to rethink how some of its most basic tenets apply in the digital sphere. Finally, as a result of the recent COVID-19 and Ukrainian crises, the EU has embraced the goal of improving the resilience of its industry. In sum, the challenge is to ensure that EU competition policy remains ‘fit for purpose’ while contributing to the transition towards a ‘green, digital and resilient single market’. Because of the structural and long-term implications of this challenge, it is apposite to refer to this transformative moment as the ‘strategic’ turn in EU competition law....
Keywords: Competition Law; ODS 16 - Paz, justicia e instituciones sólidas